Aktywacja pamięci autobiograficznej jako jeden z czynników wspierających aktywne uczenie się na lekcji języka obcego - Bielicka, Małgorzata (Neofilolog, 2010)
The present paper focuses on one of the theories supporting affect in foreign language learning, namely the theory of autobiographical memory. In contrast to mother tongue use, interaction during a foreign language lesson is a one-dimension-phenomenon taking place „here and now” that does not register in the personal history of the learner. Activation of the autobiographical memory could overcome these limitations. After the presentation of the characteristics of autobiographical memory, such as the emotional index and its relation to the time and place of the situation, the ways of activating it during foreign language lessons will be described.